Analisis Konsep Non Maleficience pada Pasien dengan Diabetes Melitus - Caryanto, Valerio Basuni Carlo; Awaludin, Sidik (Fakultas Ilmu-ilmu Kesehatan Universitas Jenderal Soedirman, 2025)
Background. Non-maleficence is an ethical principle in the field of nursing. This concept is often used in patient care in carrying out or providing nursing actions. Non-maleficence in patients with diabetes mellitus refers to actions that do not cause harm or harm to the patient Methods. Analyze this concept carried out with the help of literature on non-maleficence obtained throughGoogle Scholar and Online Books database. The keywords used are